Multi-core optical fibre shape sensing with femtosecond laser inscribed bridging cladding waveguides - Kalli, Kyriacos; Theodosiou, Antreas; Stojanovic, Stefan; Ioannou, Andreas (My University, 2019)
Femtosecond (fs) lasers are well suited for high-resolution inscription in transparent materials of all types, and in particular optical fibres. We use the versatility afforded by combining fs lasers and optical fibres to realise cladding integrated circuits that we term "bridging waveguides"; in this case we consider coupling between the displaced cores of different types of optical fibres. In particular, this new, direct, and efficient coupling technique is used to couple light from one core to multi-core optical fibres, once the two fibre types have been fusion spliced. We add further versatility by incorporating several fibre Bragg grating (FBG) arrays that are inscribed into three of the four cores of a four-core fibre. The bridging waveguides direct light from the single core fibre (SMF28) to the four-core fibre and recover the reflection spectra, so that the single core fibre can be connected to a conventional spectrometer, allowing for standard FBG characterization and demodulation. We can selectively inscribe the bridging waveguides and monitor the growth of the FBG arrays or first inscribe the FBGs and assess the quality of the waveguides in recovering the FBG spectra. The response of the FBGs after the inscription were measured and calibrated for bend and shape sensing.
Keywords: Fibre Bragg gratings; Multi-core optical fibre; Shape sensing